2021
DOI: 10.7240/jeps.693143
|View full text |Cite
|
Sign up to set email alerts
|

Geçiş Metali Katkılı ZnO’in Ferromanyetizma ve Büyüme Korelasyonunun İncelenmesi

Abstract: In this study, a series of 3d transition metal (TM) (Co, Ni and Fe) doped ZnO particles synthesized by simple co-precipitation method. Structural, morphological and magnetic properties were investigated to determine correlation between growth process and ferromagnetism of metal doped ZnO samples. All samples had ZnO hexzagonal würtzite structure and slightly shift of ZnO indexed peaks was observed by TM incorporation in ZnO. Although ZnO samples had granular forms, agglomerative forms had emerged in TM:ZnO sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…It is shown that observed high NiO crystallinity with nickle clusters in NS2 samples have improved effect on the NiO magnetism. Ferromagnetic and diamagnetic interaction may be contribute magnetic properties by uncompansated magnetic spins including nickel ions in magnetic systems that similar attitude was investigated for metal doped ZnO particles in our previous study[23]. In addition, surface defects may ensure contribution an increase magnetization with observed green band emission in Fig.4[24].…”
supporting
confidence: 59%
“…It is shown that observed high NiO crystallinity with nickle clusters in NS2 samples have improved effect on the NiO magnetism. Ferromagnetic and diamagnetic interaction may be contribute magnetic properties by uncompansated magnetic spins including nickel ions in magnetic systems that similar attitude was investigated for metal doped ZnO particles in our previous study[23]. In addition, surface defects may ensure contribution an increase magnetization with observed green band emission in Fig.4[24].…”
supporting
confidence: 59%